Customs authorities as subjects of customs control after the release of goods - Mishin, Konstantin Dmitrievich (Административное и муниципальное право, 2025)
The subject of the study is the norms of law governing the legal status of customs authorities in the implementation of customs control after the release of goods. The purpose of the work is to analyze the legal status of subjects of customs control, identify and resolve problematic aspects that arise during customs control after the release of goods. The relevance of the work is due to the fact that customs control after the release of goods allows to ease administrative pressure on persons moving goods across the customs border of the Eurasian Economic Union at the stage of customs operations before the release of goods, and also helps to ensure a balance between the application by customs authorities of customs facilitation procedures and procedures for monitoring compliance with the customs legislation of the EAEU and the legislation of the Russian Federation Of the Russian Federation on customs regulation. A set of general scientific methods of cognition was used: analysis, synthesis, analogy, deduction, induction. The most important role was played by special legal methods. In particular, the authors actively used the formal legal method, which made it possible to analyze and interpret the norms of current legislation. The logical method, the method of system-structural analysis, and the comparative legal method were also used. As a result of the scientific research, the following conclusions were obtained: 1.The orientation of the activities of customs authorities is established to maintain a balance of public and private interests, to stimulate the conscientious behavior of participants in foreign economic activity. Customs control is becoming not only a control tool, but also a tool for preventing violations of customs legislation. 2.The absence of the concept of "customs audit" in the legislation of the EAEU, which contradicts international legislation (the Kyoto Convention) and national legislation (Strategy 2030). It is necessary to regulate the customs audit, but the question remains which category it belongs to. Based on the concept of customs control, customs audit cannot be attributed to either forms or measures of customs control, therefore, it seems possible to propose introducing into customs activities a new legal entity that is a subject of activity in the field of customs affairs, included in the register of customs authorities, performing customs audit, i.e. providing a service to assess the activities of participants in foreign economic activity compliance with customs legislation The EAEU. The relevant articles regulating the legal status of the customs auditor should be included in Section VIII of the EAEU Customs Code "Activities in the field of customs affairs. An authorized economic operator."